Iron‐Catalyzed Regioselective Synthesis of 2‐Arylbenzoxazoles and 2‐Arylbenzothiazoles via Alternative Reaction Pathways. Issue 19 (17th March 2020) - Henry, Martyn C.; Abbinante, Vincenzo Mirco; Sutherland, Andrew
Abstract : A one‐pot regioselective method for the preparation of 2‐arylbenzoxazoles from N ‐arylbenzamides has been developed using iron(III)‐catalyzed bromination of the aryl ring, followed by copper(I)‐catalyzed O ‐cyclization with the benzamide side chain. In contrast, reaction of N ‐arylthiobenzamides with N ‐bromosuccinimide and iron triflimide led directly to the isolation of the corresponding 2‐arylbenzothiazoles via intramolecular C–S bond formation. Mechanistic and control experiments suggest that in this case, bromination occurs at the sulfur atom, resulting in a reactive intermediate that can undergo electrophilic aromatic substitution and S ‐cyclization. The scope of both processes was explored yielding a range of structural analogues, including a pharmaceutically active compound for the treatment of Duchenne muscular dystrophy and an affinity agent of the amyloid‐beta protein in Alzheimer's disease. Abstract : Methods involving iron‐catalysis for the synthesis of 2‐arylbenzoxazoles and 2‐arylbenzotriazoles from the corresponding N ‐arylbenzamide or N ‐arylthiobenzamide have been developed. While the aryl ring of N ‐arylbenzamides are activated by bromination and then cyclized by copper‐catalysis, treatment of N ‐arylthiobenzamides with NBS led directly to the cyclized product.